Revealing the working mechanism of polymer photodetectors with ultra-high external quantum efficiency. Issue 45 (3rd November 2015) - Li, Lingliang; Zhang, Fujun; Wang, Wenbin; Fang, Yanjun; Huang, Jinsong
Abstract : Only the trapped electrons in PC71 BM near the Al electrode are beneficial to hole tunneling injection from the Al electrode. Abstract : We report polymer photodetectors (PPDs) with an evident photomultiplication (PM) phenomenon, based on a sandwich structure ITO/PEDOT:PSS/P3HT:PC71 BM(100:1)/Al. A similar device structure has been reported in our previous work, showing great potential as a new type of high performance PPD. However, we found more interesting new phenomena from these PPDs. Solid evidence is provided to prove the existence of photogenerated electron transport in the almost hole-only active layer under an applied bias. The transport of photogenerated electrons leads to electron accumulation near the Al electrode and the electron redistribution, which strongly affect the EQE spectral shape and the transient response of the PPDs. Our conclusion is further confirmed by confirmatory devices with a structure of Al(1)/P3HT:PC71 BM(100:1)/Al(2). EQE spectra and transient J ph curves of the confirmatory devices accord well with our speculation. This discovery may provide a new insight to increase the response speed of PM type PPDs by adjusting the photogenerated electron distribution in the active layer. Considering that the PM type PPDs have much higher EQE than the traditional organic photodetectors, the improvement may further extend its potential applications with low cost.